Revitalizing the Value of Educational Innovation During the Golden Age of Islam in Facing Global Challenges - Nurazis, Taufiq (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2025)
This study critically analyzes and evaluates the core philosophical and structural educational innovations developed during the Islamic Golden Age (8th to 13th centuries AD) and their specific relevance in addressing three critical contemporary global educational challenges: the knowledge dichotomy (secularization), the character crisis, and the global competency gap. The research employs a qualitative-descriptive method, utilizing a literature study approach (Library Research) and focused contextual comparative analysis. Primary and secondary data were sourced from historical accounts of key Islamic educational institutions Bayt al-Hikmah and Madrasah systems, classical Islamic philosophy of science, and contemporary literature on global educational demands (e.g., 21st Century Skills and the impact of digitalization). The analysis follows a three-stage framework: 1) Historical Analysis of Golden Age innovations; 2) Critical Evaluation of the identified innovations' potential to resolve contemporary challenges by operationalizing them against modern structural and philosophical variables (such as pragmatism and secularization); and 3) Constructive Synthesis to formulate practical pillars of revitalization rooted in Qur'anic values. The findings propose six interconnected pillars of revitalization, specifically targeting systemic deficiencies: paradigm revitalization (eliminating the curriculum dichotomy), ecosystem revitalization, methodology, institutional structure, teaching staff development, and pedagogical orientation. In conclusion, the revitalization of Islamic education is framed as a systematic effort to re-embody the spirit of iqra (reading and researching), leveraging the intellectual and ethical strengths of classical traditions to build a bridge to the future. This effort aims to transition Islamic education from being merely a follower of change to becoming a renewed source of civilization and innovation that effectively integrates spiritual depth with global competence.